Meningkatkan Kemampuan Menyimak Melalui Metode Bercerita Dengan Big Book Pada Anak Usia 5-6 Tahun di TK Nurul Huda Srikaton - Widaningsih Widaningsih; Nuryanah Nuryanah; Hariyanti Hariyanti; Helen F Sinambela (Jurnal Pendidikan Tuntas, 2023)
Developing good listening skills from an early age provides a strong foundation for children's future learning and interaction abilities. By providing the right attention and approach, a child's listening ability can be improved significantly, although it is difficult to measure the level of mastery directly. The aim of this research is to improve listening skills through the use of Bigbook media for group B children aged 5-6 years at Nurul Huda Srikaton Kindergarten. Furthermore, this research was carried out in two cycles and each cycle was held in two meetings. This research was carried out at Nurul Huda Srikaton Kindergarten with research subjects being Group B aged 5-6 years, totaling 11 people. Data collection in this research used observation and documentation techniques. The research results were that in cycle 1, 27.27% of children were still in the underdeveloped category, whereas after cycle 2 it was 0%. Furthermore, in cycle 1 there were 27.27% of children who were still in the beginning to develop category, then in the second cycle it was 9.09%. A significant increase occurred in the category developing as expected, namely from 18.18% increasing to 72.73% of children. Furthermore, the very well developed category in cycles 1 and 2 both received a score of 18.18%. This shows that the learning and development efforts carried out on children have provided positive results, with the majority of children showing improvements in listening skills in line with the expectations that have been set. Keywords: Listening Ability, Bigbook Media, ECE